Air transport security issues, challenges and national policies - Szyliowicz, Joseph S.; Zamparini, Luca (Edward Elgar Publishing, 2018)
"This timely book provides a multidisciplinary and comparative analysis of the ongoing terrorist threats against all aspects of air transportation, the effectiveness of the responses, globally, regionally and nationally, and the continuing challenges to policymakers seeking to achieve a safe and secure global aviation system. The first part provides an overview of the industry's characteristics, the economic and regulatory issues shaping the security environment, such as legal frameworks, and the role of the private sector in safeguarding passenger and air cargo flights. The second part provides comparative analyses of security policies and practices in several key countries: the United States, Canada, Brazil, Kenya, Israel, Malaysia, Japan and Australia. The book concludes with a comparative analysis of the contemporary state of aviation security policies and practices and its future challenges. Containing extensive interdisciplinary analyses of the main issues and challenges related to all aspects of aviation security, the book will be of great interest not only to scholars, students and practitioners concerned with aviation security, and to institutions that provide courses or programs in aviation management and related fields, but also to anyone dealing with such related topics as terrorism, public policy, transport, urban studies and logistics."--From publisher's website
Literaturangaben
Keywords: Luftverkehr; Sicherheitsmaßnahme; Air travel / Security measures; Air travel / Safety measures; Aufsatzsammlung